2023
DOI: 10.3389/fnins.2023.1226181
|View full text |Cite
|
Sign up to set email alerts
|

TUBB3 and KIF21A in neurodevelopment and disease

Abstract: Neuronal migration and axon growth and guidance require precise control of microtubule dynamics and microtubule-based cargo transport. TUBB3 encodes the neuronal-specific β-tubulin isotype III, TUBB3, a component of neuronal microtubules expressed throughout the life of central and peripheral neurons. Human pathogenic TUBB3 missense variants result in altered TUBB3 function and cause errors either in the growth and guidance of cranial and, to a lesser extent, central axons, or in cortical neuronal migration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 176 publications
(264 reference statements)
0
3
0
Order By: Relevance
“…[37] In addition, abnormal expression of KIF21A, an anterograde kinesin-motor protein that directly interacts with microtubules, plays an important role in various nervous system related diseases in humans. [38] IA formation is characterized by destruction of and cystic formation in arterial wall. Animal studies have suggested that pathological changes of vascular smooth muscle cells in tunica media is an important part of formation of aneurysms, which were also confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] In addition, abnormal expression of KIF21A, an anterograde kinesin-motor protein that directly interacts with microtubules, plays an important role in various nervous system related diseases in humans. [38] IA formation is characterized by destruction of and cystic formation in arterial wall. Animal studies have suggested that pathological changes of vascular smooth muscle cells in tunica media is an important part of formation of aneurysms, which were also confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 ] In addition, abnormal expression of KIF21A, an anterograde kinesin-motor protein that directly interacts with microtubules, plays an important role in various nervous system related diseases in humans. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…The c.-115C>G and c.*286A>T variants of TUBB3 could give rise to the dysfunction of neuronal-specific β-tubulin isotype III, which may lead to compound cortical dysplasia with other brain developmental abnormalities type 1 associated with the syndrome of MRD7, however, the location of TUBB3 variant is in the non-coding region and comprehensively estimated as LP. The c.194C>T and c.874A>G variants of NALCN were inherited from proband’s father and were estimated as VUS, her father did not show the symptoms of the same variants of NALCN and the certain variants’ pathogenic proof were not retrieved in the database presented as before ( Radwitz et al, 2022 ; Puri et al, 2023 ). The 16p12.2del variants were inherited from the proband’s mother, which was estimated as pathogenic for her mother’s corresponding symptoms.…”
Section: Discussionmentioning
confidence: 99%